An essential pentatricopeptide repeat protein in the apicomplexan remnant chloroplast. (16th September 2019) - Hicks, Joanna L.; Lassadi, Imen; Carpenter, Emma F.; Eno, Madeleine; Vardakis, Alexandros; Waller, Ross F.; Howe, Christopher J.; Nisbet, R. Ellen R.
Abstract: The malaria parasite Plasmodium and other apicomplexans such as Toxoplasma evolved from photosynthetic organisms and contain an essential, remnant plastid termed the apicoplast. Transcription of the apicoplast genome is polycistronic with extensive RNA processing. Yet little is known about the mechanism of apicoplast RNA processing. In plants, chloroplast RNA processing is controlled by multiple pentatricopeptide repeat (PPR) proteins. Here, we identify the single apicoplast PPR protein, PPR1. We show that the protein is essential and that it binds to RNA motifs corresponding with previously characterized processing sites. Additionally, PPR1 shields RNA transcripts from ribonuclease degradation. This is the first characterization of a PPR protein from a nonphotosynthetic plastid.